Inclusive χbJ(nP) decays to D0X - Briere, R; Ferguson, T; Tatishvili, G; Vogel, H; Watkins, M; Rosner, J; Alexander, J; Cassel, D; Duboscq, J; Ehrlich, R; Fields, L; Galik, R; et al. (2008)
Using Υ(2S) and Υ(3S) data collected with the CLEO III detector we have searched for decays of χbJ to final states with open charm. We fully reconstruct D0 mesons with pD0>2.5GeV/c in three decay modes (K-π+, K-π+π0, and K-π-π+π+) in coincidence with radiative transition photons that tag the production of one of the χbJ(nP) states. Significant signals are obtained for the two J=1 states. Recent nonrelativistic QCD (NRQCD) calculations of χbJ(nP)→cc̄X depend on one nonperturbative parameter per χbJ triplet. The extrapolation from the observed D0X rate over a limited momentum range to a full cc̄X rate also depends on these same parameters. Using our data to fit for these parameters, we extract results which agree well with NRQCD predictions, confirming the expectation that charm production is largest for the J=1 states. In particular, for J=1, our results are consistent with cc̄g accounting for about one-quarter of all hadronic decays. © 2008 The American Physical Society.